Hydrogen peroxide positively regulates ABA signaling via oxidative modification of the C2H2-type zinc finger protein ZFP36 in rice - Ji, E (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.